Authentic Assessment in Islamic Religious Education: Measuring Students’ Holistic Competencies through Performance-Based Evaluation - Mahmoud Abdullah; Huzaiman Hushin; Salma Begum; Yousif Mahmadov; Abdallah El-Khatib (PT Barkah Ilmi Fiddunya, 2026)
Assessment in Islamic Religious Education has traditionally focused on measuring cognitive achievement, often neglecting students’ affective and behavioral competencies. This study aims to develop an authentic assessment model capable of comprehensively evaluating students’ knowledge, attitudes, skills, and religious practices. A research and development methodology employing the Borg and Gall model was utilized. The study involved curriculum experts, Islamic education teachers, and secondary school students during instrument development, validation, pilot implementation, and evaluation stages. Data were analyzed using content validity, reliability testing, and descriptive statistics. The findings indicate that authentic assessment using portfolios, reflective journals, project evaluations, self-assessment, peer assessment, and performance tasks provides a more comprehensive understanding of students’ learning outcomes. Teachers also reported greater effectiveness in monitoring students’ character development, religious practice, and collaborative skills. The assessment model aligns well with competency-based curricula and supports continuous learning improvement. The novelty of this study lies in constructing a Holistic Authentic Assessment Framework specifically designed for Islamic Religious Education, integrating cognitive, affective, psychomotor, and spiritual domains into a unified evaluation system